(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The article presents the need for the development of farming on an innovative basis, important features and factor analysis of innovative development of agricultural farming, approaches to the implementation of an organic farming system.